2022
DOI: 10.1177/09564624211056749
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections incidence in young Thai men who have sex with men and transgender women using HIV pre-exposure prophylaxis

Abstract: Background Sexually transmitted infections are a major public health issue worldwide. HIV pre-exposure prophylaxis (PrEP) use among youth may be associated with increased incidence of sexually transmitted infections (STIs). Objectives To measure the prevalence and incidence of STIs among young men who have sex with men (YMSM) and young transgender women (YTGW) using PrEP. Methods A prospective cohort of 15- to 19-year-old YMSM and YTGW with HIV risk defined as inconsistent condom use and/or multiple sex partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Based on national HIV sentinel surveillance of MSM aged 16 years or older in Vietnam, factors associated with HIV infection included place of residence, early sexual debut, consistent condom use and not engaging in anal sex during the past month, not knowing one's HIV test results, having ever injected drugs, and having active syphilis [ 14 ]. In another study, it was reported that factors associated with STI incidence were self-reported >2 sex partners in the past month (unadjusted rate ratio [uRR] 4.6, 95% CI 1.0, 20.6), and moderate preexposure prophylaxis (PrEP) adherence ([uRR] 7.3, 95% CI 1.6, 32.6) in young Thai MSM [ 27 ]. A retrospective study in Shenzhen, China found that ever had sex with female, gender of the first sexual partner, marital status, age group, education, monthly income (RMB), frequency of condom use in anal sex with men in the past 6 months, and history of STIs were significantly associated with herpes simplex virus type 2 (HSV-2 infection).…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Based on national HIV sentinel surveillance of MSM aged 16 years or older in Vietnam, factors associated with HIV infection included place of residence, early sexual debut, consistent condom use and not engaging in anal sex during the past month, not knowing one's HIV test results, having ever injected drugs, and having active syphilis [ 14 ]. In another study, it was reported that factors associated with STI incidence were self-reported >2 sex partners in the past month (unadjusted rate ratio [uRR] 4.6, 95% CI 1.0, 20.6), and moderate preexposure prophylaxis (PrEP) adherence ([uRR] 7.3, 95% CI 1.6, 32.6) in young Thai MSM [ 27 ]. A retrospective study in Shenzhen, China found that ever had sex with female, gender of the first sexual partner, marital status, age group, education, monthly income (RMB), frequency of condom use in anal sex with men in the past 6 months, and history of STIs were significantly associated with herpes simplex virus type 2 (HSV-2 infection).…”
Section: Text Of Reviewmentioning
confidence: 99%